Internal Structure of a Scale of Helplessness for young people in northern Mexico - Gonzalez Tovar, Jose (2019)
Objective. Analyze the internal structure of the proposal for a Youth Helplessness Scale (EIJ, by its acronym in Spanish) in a sample of the city of Saltillo, Coahuila, Mexico. Method. A quantitative methodology of instrumental design was used. An incidental sample of 750 cases was chosen, of which 50.3% were men and 49.7% women, and whose average age was 21.85. A Scale of Hopelessness for Young people consisting of 47 reactants was used, measuring affection, motivation, cognition and behavior. The reliability was. 898, and an exploratory and confirmatory factor analysis was carried out. Results. Adjustment indices met the criterion of good fit. This tool provides a way to measure the predictor variables of suicidal behavior, all of which constitute a current public health problem, and which are partly predicted by indicators of helplessness.